Congenital toxoplasmotic chorioretinitis following reinfection. (August 2020) - Giugno, Salvatore; Monteleone, Morena Maria; Insalaco, Giulio; Leanza, Gianluca; Palumbo, Marco; Leanza, Vito
Abstracts: Toxoplasmosis does not usually give any symptoms to a pregnant woman and in most cases she does not realize to be infected. On the contrary, in the newborn, congenital toxoplasmosis can be responsible of hydrocephalus, microcephaly, intracranial calcifications, strabismus, blindness, epilepsy, mental retardation, thrombocytopenia, anemia and chorioretinitis. All these pathologies have been reported in the primary infection, while they are unusual in either reinfections or recurrences. We report two rare cases of reinfection of the mother during pregnancy where the neonates showed chorioretinitis.